(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2020)
The transition to a market economy, the privatization of manufacturing and the sale of goods in Ukraine have led to a rapid increase in the number of independent enterprises, which has resulted in a weakening of state control and supervision over the quality and safety of products. The problem of quality has become acute social in nature. Because of this, a great deal of material and moral damage is caused, and millions of Ukrainians are at risk of health and life. The article investigates methods and means of falsification of foodstuffs, analyzes the foreign and domestic experience of combating this phenomenon. Also outlined are ways that can prevent food counterfeiting in the domestic consumer market. The factors that lead to such a high level of fraud in the country are: lack of harmonized governance, imperfection of the legal framework; economic problems; weakening of state control and observation and lack of overall coordinating control bodies; lack of certification effectiveness; there is no strict responsibility of sellers for selling counterfeit products. The article gives specific examples of assortment of information and qualitative falsification of food products. Today, the problem of food expertise has already gone beyond the interests of individual laboratories, scientific institutions and even states. In Ukraine, requirements for the development and implementation of food safety management systems are set by the relevant Laws, conditions are created for competition between private and public laboratories and the cost of relevant research is reduced. However, despite significant achievements in the field of counterfeiting and improving the quality and safety of products in Ukraine, which in the world as a whole face new problems: the scale of use of food additives is increasing every year, one of the modern directions of biotechnology - creation of transgenic food products is intensively developing. Therefore, the fight against food fraud should be undertaken in the following ways: development of new and improvement of existing methods of examination, creation of a coordination center for the collection, analysis and publication of analytical results obtained by individual centers and laboratories for the quality of food and raw materials; joint participation of Ukraine with the International organizations in the development of more sophisticated counterfeit detection devices; - adaptation of Ukrainian legislation to the requirements of EU legislation in the field of food quality regulation; development of methodology for evaluation of technical documentation regarding the ability of new equipment to produce quality and safe products; creating conditions for competition between private and public laboratories and reducing the cost of relevant research; mandatory inclusion of food producers in the Only Original system.